Analysis Of The Reading Literacy Level Of Fourth Grade Students In Solving Indonesian Language Story Problems At SD Inpres Perumnas Antang III - Bangsawan, Andi Aryanto; Hermuttaqien, Bhakti Prima Findiga; Hartoto, Hartoto (Program Studi PGSD FIP UNM, 2025)
This research aims to analyze the literacy levels of fourth-grade students at Inpres Perumnas Antang III Elementary School in solving story problems and to identify the supporting and inhibiting factors. The research method uses a qualitative approach with data collection techniques through participatory observation, in-depth interviews with 29 students and 1 teacher, as well as document studies. The results show that the literacy levels of students are divided into three categories: low literacy (Students have difficulty understanding explicit information in the text and relating it to simple contexts.), moderate literacy (Students are able to understand explicit information and some implicit information in the text, but are not yet consistent in summarizing or evaluating the content.), and high literacy (Students are able to analyze complex texts, evaluate implicit information, and critically reflect on moral messages). The main inhibiting factors include conventional teaching methods, a lack of practice with story problems, and The learning environment is less interactive. Meanwhile, supportive factors include the School Literacy Movement (GLS) program, the use of visual media, and support from teachers and parents. This research recommends the implementation of differentiated learning approaches, strengthening metacognitive strategies, and optimizing the learning environment to improve student literacy. These findings serve as a basis for the development of education policies and learning practices that focus on student needs.